Three-Month Follow-Up of Heterologous vs. Homologous Third SARS-CoV-2 Vaccination in Kidney Transplant Recipients: Secondary Analysis of a Randomized Controlled Trial - Heinzel, Andreas; Schrezenmeier, Eva; Regele, Florina; Hu, Karin; Raab, Lukas; Eder, Michael; Aigner, Christof; Jabbour, Rhea; Aschauer, Constantin; Stefanski, Ana-Luisa; Dörner, Thomas; Budde, Klemens; et al. (Frontiers in Medicine, 2022)
Response to SARS-CoV-2-vaccines in kidney-transplant-recipients (KTR) is severely reduced. Heterologous 3rd vaccination combining mRNA and vector vaccines did not increase seroconversion at four weeks after vaccination but evolution of antibody levels beyond the first month remain unknown. We recently completed a randomized-controlled-trial on heterologous (Ad26COVS1) vs homologous (BNT162b2 or mRNA-1273) 3rd vaccination in 201 KTR not developing SARS-CoV-2-spike-protein-antibodies following two doses of mRNA vaccine (EurdraCT: 2021-002927-39). Here we report seroconversion at the second follow-up at three months after the 3rd vaccination (prespecified secondary endpoint). In addition, higher cut-off levels associated with neutralizing capacity and protective immunity were applied (i.e. >15,>100,>141 and >264 BAU/mL). A total of 169 patients were available for the three-month follow-up. Overall, seroconversion at three months was similar between both groups (45% versus 50% for mRNA and vector group, respectively; p=0.539). However, when applying higher cut-off levels, a significantly larger number of individual in the vector group reached antibody levels >141 and >264 BAU/mL at the three-month follow-up (141 BAU/mL: 4% vs. 15%, p=0.009 and 264 BAU/mL: 1% vs. 10%, p=0.018 for mRNA vs. vector vaccine group, respectively). In line, antibody levels in seroconverted patients further increased from month one to month three in the vector group while remaining unchanged in the mRNA group (median increase: mRNA= 1.35 U/mL and vector = 27.6 U/mL, p = 0.004). Despite a similar overall seroconversion rate at three months following 3rd vaccination in KTR, a heterologous 3rd booster vaccination with Ad26COVS1 resulted in significantly higher antibody levels in responders.